Exploring the Problems and Challenges of Micro, Small and Medium Enterprises in Northern Province - Sathana, V.; Velnampy, T. (Macrothink Institute, 2019)
The purpose of this study is to identify the problems and challenges of SMEs in the postwar situation of Northern Province. Researcher conducted qualitative exploratory research; explain the phenomenon of problematic situation of SMEs in Northern Province. By applying purposive sampling technique, with primary data collection method of focus group discussion and interviews were conducted with the owners of SMEs and officers related with the SMEs in the Northern Province. Finding of the study explains, first, marketing problems which includes product problems, pricing problems, promotion problem, distribution based problems, green problem and network problems, second, internal problem which includes financial problems and employee problems third, characteristics of entrepreneurs as problems, at last external problems, namely political and legal, economic and socio economic problems.The important implication is that this study indicates clearly the problems and challenges of SMEs in the post war market. It will help the owners of SMEs the means to solve these problems, and govern officers to understand the means to support the SMEs.
Keywords: Problems and challenges; Micro, Small and Medium Enterprises (SMEs); Post war market